If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65x + 50y = 63 Solving 65x + 50y = 63 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-50y' to each side of the equation. 65x + 50y + -50y = 63 + -50y Combine like terms: 50y + -50y = 0 65x + 0 = 63 + -50y 65x = 63 + -50y Divide each side by '65'. x = 0.9692307692 + -0.7692307692y Simplifying x = 0.9692307692 + -0.7692307692y
| 3x^2(x-3)+7x(x-3)-20(x-3)=0 | | p=300-2w-2l | | -7x+3=10 | | -8=33-5q | | 10x^2=14-8x | | 3/5x-x/4=-2 | | 6w-w=40 | | 4x-11=-5(-7x-4) | | 6/4(x-3) | | 6+(52-5)2=p | | (9x-40)= | | 17-13*6*x= | | 5b^2+6=851 | | 27x-5=9x+5 | | y=5x-10is | | 36m^2-25=0 | | 5a-2=5a-2 | | 18=m+n | | b^2+7=33 | | 18=15-m | | 300x^4+1000x^2+300=0 | | 3cosx+2sinx=2.5 | | 3x(2x-8)= | | 45=5c+15 | | 2+-1x=x | | 9(7+x)=270 | | 0.6r=405 | | 3z+i=5-iz | | 2(r-6)--7=9 | | h/68 | | 5-(x+1)+2x=8 | | -9(x-2)=20-11x+9 |